Pentingnya Pendidikan Agama Islam dalam Membentuk Karakter Anak - Somad, Momod Abdul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This research is motivated by our curiosity and public anxiety over the various characters of a child or individual in Indonesia. The hope of the community is big enough to make a child or individual able to get good character education, so that he becomes a human with character, has noble character and can live his life in accordance with Islamic law. Seeing this, it is necessary to conduct a study of this incident by taking samples from various examples in the community who are or have undergone the process of educating their children. Researchers conducted surveys and asked questions with people around and got various kinds of responses that were quite diverse. To achieve this goal, this research uses qualitative-descriptive research methods with literature study techniques. The results of this study obtained data and facts that character education from an early age is very important, by choosing the right methods according to Islamic teachings so that children become human beings who are educated in faith, science, charity, have broad insight, become good citizens and noble character that can benefit all mankind.